Evaluation of Slope Stability within the Influence of Mining Based on Combined Weighting and Finite Cloud Model - Chen, Hongkai; Guo, Qingbiao; Wang, Liang; Meng, Xiangrui (Energy exploration & exploitation, 2023)
Coal mining under slopes often leads to slope instability, resulting in substantial economic losses and human casualties. Therefore, constructing a scientific and practical slope stability evaluation model for slope disaster prevention and control is of great significance. In this study, seven evaluation indexes were selected, and their influence mechanisms were analyzed to establish a system of evaluation indexes for the stability of mining slopes in Xing County, Shanxi Province, China. A new evaluation model for the stability of mining slopes was established based on the interval analytic hierarchy process (IAHP) to determine the subjective weights of the indexes and the improved CRITIC method to determine the objective weights of the indexes, which circumvented the limitations of subjective or objective weights by combining the minimum discriminating information. The model was applied to the mining slopes in Xing County, Shanxi Province, and the results showed that slopes A, C, D and E were in an unstable state, slope B was in an understable state after mining. Finally, the accuracy of the evaluation results was verified through field surveys. The model has engineering application value in predicting the stability of mining slopes and can provide theoretical suggestions for later slope management to ensure the safe production of coal mines.